The Early Outcomes of BeGraft Peripheral Plus in Branched Endovascular Repair of Thoracoabdominal Aneurysms. (October 2021) - Abisi, Said; Gkoutzios, Panos; Carmichael, Michelle; Patel, Sanjay; Sallam, Morad; Donati, Tommaso; Zayed, Hany
Objective: No bridging stent-graft (BSG) has been specifically designed for branched endovascular aortic repair (BEVAR) and therefore different "off-label" stent-grafts have been used. Recently, a third generation of balloon-expandable stent-graft has become available. Here we evaluate the outcomes of the BeGraft Peripheral Plus (B+) used as a BSG for internal/externalor inner branches during BEVAR. Materials and Methods: Consecutive patients undergoing BEVAR using B+ as a BSG since its release in 2017 were included into the study. The primary endpoints were technical success and target vessel patency during follow-up. Secondary endpoints included the need for adjunct extension and relining of the BSG, branch instability rate, including occlusion, reinterventions for restonosis, kink, fracture, or endoleak (types 1 and 3). Results: A total of 163 visceral branches in 46 patients were included with a median follow-up 15 months (4–36 months). Primary technical success was achieved in all visceral branches (69 inner branches and 94 internal/external branches) with the exception of 1 BSG that required serial dilatation until full expansion was achieved with overall branch patency was 98% at 2 years. An additional stent-graft was necessary in 35 branches (21%) following deployment of a B+ BSG to cover a longer bridging distance and optimize the distal and proximal sealing. Relining of B+ BSG was not routinely carried out during the index procedure and a self-expanding uncovered nitinol stent was necessary in only 3% of branches to smooth the distal transition zone between the BSG and target vessel. There were 4 events (2.4%) of branch related instability, including 2 occlusions and 2 late reinterventions for a partial in-stent-graft thrombosis. Conclusion: Our study findings show satisfactory early outcomes of B+ as a BSG in BEVAR with low occlusion and reintervention rates. Extensions of BSG might be required to achieve adequate seal in the target vessels but routine relining BSG in branches was not required.